2022
DOI: 10.1002/admt.202200339
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Approach for Preparing Shape‐Morphing Bilayer Films by Simply Adhering Two SEBS/Paraffin Films with Different Deformability and Melting Temperatures

Abstract: Shape‐morphing materials that can exhibit various shape deformations are highly desirable. In this work, shape‐morphing materials with diverse deformation modes are prepared via a facile approach of constructing bilayer structures of SEBS/paraffin blends with different melting temperatures. The bilayer films are prepared using a simple solvent‐coating adhesion method, either by adhering two single‐layers together and stretching or by adhering two pre‐stretched single‐layers. These bilayer films show strong int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…The SEBS/paraffin system, which contained a crystallizable fixing phase (paraffin) and an elastic recovering phase (SEBS), was a kind of interesting shape memory material. [29][30][31][32][33] Utilizing the shape memory properties of the material, it could be used as a wearable device that could be firmly attached to various parts of the human body. Here, the shape memory properties of the SPWTPP phase change foaming film were tested, and the results are shown in Fig.…”
Section: Papermentioning
confidence: 99%
“…The SEBS/paraffin system, which contained a crystallizable fixing phase (paraffin) and an elastic recovering phase (SEBS), was a kind of interesting shape memory material. [29][30][31][32][33] Utilizing the shape memory properties of the material, it could be used as a wearable device that could be firmly attached to various parts of the human body. Here, the shape memory properties of the SPWTPP phase change foaming film were tested, and the results are shown in Fig.…”
Section: Papermentioning
confidence: 99%
“…Beyond our fundamental interest in plasticity effects in layered systems, [5][6][7][8] we are motivated by the potential for origami engineering where shape morphing can be induced in metal-plastic laminates by a simple loading-unloading protocol. Indeed such a stretch-release approach to origami has been explored previously, [1,3,4,[9][10][11] and Nelson et al [3,4] have coined the DOI: 10.1002/adem.202301111…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al [9] showed especially beautiful examples of complex shapes realized by this approach. The permanent deformations in the past research were attributable to various mechanisms: plasticity of semicrystalline polymers [5,12] or of paraffin waxes, [11] plasticity of a crystallizable wax used as swelling agent, [9] or charge interactions in a polymer network. [3,4] In contrast, this article exploits the plasticity of metals beyond their yield point.…”
Section: Introductionmentioning
confidence: 99%